LEARNING STRATEGIES OF HIGH ACHIEVEMENT STUDENTS IN ENGLISH OF SMA DHARMA PANCASILA MEDAN - Sisca Indayani Damanik; Masitowarni Siregar (Universitas Negeri Medan, 2021)
Learning English is one of the important things for students to acquire English well. Many students are still confused to choose what are the strategies that appropriate for them. Several strategies can be used for students to get higher achievement. Meanwhile, students have individual characteristics related to their learning processes, the used of the strategies will give big impact for their achievement. Students whose have high achievement also have their own strategies in their learning process. This is why this research interesting. The objective of the study was known what are the learning strategies used by high achievement students of SMA Dharma Pancasila Medan. By using questioner and interviewed which is adopted from Strategy Inventory for Language Learning (SILL) version 7.0 (ESL/EFL) by Oxford (1990) translated into Bahasa Indonesia to avoid misinterpretation and misunderstanding. The study's result was based on the answers using yes/no questions to determine whether students used direct or indirect strategies, from the interview session followed by the three high achiever students of SMA Dharma Pancasila Medan. The first students tend to used memory, metacognitive and compensation strategies as the main strategies. The second high achievers employed cognitive, metacognitive, and compensation strategies as the main strategies in learning English. Meanwhile, the third used memory, cognitive and social strategy as the main strategies. The data showed the students combined all strategies in the learning process and used three strategies as the main strategy.Keywords : English, Learning Strategies, Achievement.